Liver transplantation in gastroenteropancreatic neuroendocrine tumors - Fernandes, Eduardo de Souza M.; Kyt, Camila V. Garcia; de Mello, Felipe Pedreira Tavares; Pimentel, Leandro Savattone; Andrade, Ronaldo de Oliveira; Girão, Camila; César, Camilla; Siqueira, Munique; Monachesi, Maria Eduarda; Brito, Anderson; Tavares de Sousa, Claudia Cristina; Andraus, Wellington; et al. (Frontiers in Oncology, 2023)
Neuroendocrine tumors are part of a heterogeneous group of tumors located in organs such as the gastrointestinal tract (GIT), lungs, thymus, thyroid, and adrenal glands. The most prevalent sites are the small intestine, cecal appendix, and pancreas. More than 50% of these tumors are associated with metastases at the time of diagnosis. Neuroendocrine tumors are classified according to the degree of cell differentiation and the histopathological proliferation index of the lesion. G1, G2, and G3 tumors are well differentiated. Undifferentiated or poorly differentiated tumors are considered neuroendocrine carcinoma (NEC), which is characterized by Ki-67 expression greater than 20% and is subdivided into the small-cell type and large-cell type. When the neuroendocrine tumors present clinical symptoms, compressive symptoms and carcinoid syndrome are evident. Carcinoid syndrome occurs when the tumor produces neuroendocrine mediators which cannot be metabolized by the liver due to either the size of the tumor or their secretion by the liver itself. Several therapeutic strategies have been described for the treatment of metastatic neuroendocrine tumors, including curative or palliative surgical approaches, peptide receptor radionuclide therapy, percutaneous therapy, systemic chemotherapy, and radiotherapy. Liver surgery is the only approach that can offer a cure for metastatic patients. The liver metastases must be completely resected and, in this context, orthotopic liver transplantation has gained prominence for yielding very promising outcomes in selected cases. The aim of this study is to review the literature on OLT as a form of treatment with curative intent for patients with gastroenteropancreatic neuroendocrine tumors with liver metastasis.